THE ROLE OF AI IN DETECTING INSIDER THREATS IN HEALTHCARE ORGANIZATIONS - Krunal Manilal Gala (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article explores the critical role of Artificial Intelligence (AI) in detecting and preventing insider threats within healthcare organizations. It examines the growing challenges of data security in the healthcare sector, highlighting the significant financial and reputational risks posed by insider threats. The article discusses various types of insider threats, including malicious actors, negligent employees, and compromised credentials. It then delves into how AI enhances insider threat detection through behavioral analytics, machine learning, natural language processing, and predictive analytics. The article outlines key steps for implementing AI-based insider threat detection systems and addresses the ethical considerations and privacy concerns associated with such implementations. By leveraging AI technologies, healthcare organizations can significantly improve their ability to protect sensitive patient data and maintain the integrity of their systems.